Analisis Perbandingan Fonologi Bahasa Indonesia dan Bahasa Melayu dalam Kartun Upin Upin - Sintia Pratama; Irna Yanti; Erva Siti Nurchotimah (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2023)
This study aims to determine the comparison between Indonesian and Malay from a phonological aspect by using the cartoon series "Upin and Ipin" as research subjects. The research was conducted using descriptive qualitative methods using free listening techniques. Researchers found phonetic elements in the entire Malay language that aired on the episode Season 15 Gerobok Rezeki. It has been found that Malay and Indonesian have almost the same function of stress, tone, intonation and duration in the pronunciation of vocabulary sounds. The difference between the two is the nasal sound that is more inherent in Malay. There are also differences in phonological aspects in the form of changing the vowel "a‟ to the vowel "ə‟ in some vocabulary words with the same pattern of wording and meaning.